ISLAM SEBAGAI AGAMA DAN ISLAM SEBAGAI BUDAYA DALAM MASYARAKAT BANJAR - Abdul Wahab Syakhrani; Muhammad Nafis (CV. Adiba Aisha Amira, 2022)
Islam and Banjar culture are two things that cannot be separated in the life of their religious community, such as Hari al-Shura (10 Muharram) and Al-Syura porridge, maulidan, baayun maulid, batampung Tawar, bapalas midwife, baarwahan and bahaulan. The above tradition that is increasingly rarely encountered is the midwife's bapalas. This tradition should be reintroduced to the people of South Kalimantan, especially the Banjar tribal community, whether it is carried out by the government or community leaders so that the tradition is maintained.